2019
DOI: 10.1177/1057083719867682
|View full text |Cite
|
Sign up to set email alerts
|

Music Teacher Rankings of Selected Core Teaching Practices

Abstract: There is a decades-long history of music education researchers examining characteristics and skills associated with effective teaching and assessing how preservice music teachers develop those competencies. Building on studies of pedagogical content knowledge and the professional opinions of experienced music educators, researchers are now attempting to identity a body of core music teaching practices. We asked experienced in-service music teachers ( N = 898) to think about the skills beginning music teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…The expert panel in this study was able to achieve a strong consensus on three core teaching practices: (a) modeling , (b) sequencing instruction , and (c) deconstructing musical concepts . It seems clear that being a competent musician is important inasmuch as teachers need to effectively model for their students to develop skills such as tone, technique, or music style (Millican & Forrester, in press). Music skill in this context is a pedagogical tool that allows teachers to communicate music concepts in a natural and direct way.…”
Section: Discussionmentioning
confidence: 99%
“…The expert panel in this study was able to achieve a strong consensus on three core teaching practices: (a) modeling , (b) sequencing instruction , and (c) deconstructing musical concepts . It seems clear that being a competent musician is important inasmuch as teachers need to effectively model for their students to develop skills such as tone, technique, or music style (Millican & Forrester, in press). Music skill in this context is a pedagogical tool that allows teachers to communicate music concepts in a natural and direct way.…”
Section: Discussionmentioning
confidence: 99%
“…In a word, the arrival of the new media era has given college education a new opportunity for expansion and brought many challenges. Colleges and universities should seize this opportunity to deepen the music teaching reform, change the traditional teaching idea in the past, and fully combine the new media technology and the environment with music teaching [17]. ey should implement good interaction with students, provide an open and innovative teaching environment, and finally cultivate well-rounded music talents with high quality and strong professionalism.…”
Section: Problems Of Musicmentioning
confidence: 99%
“…One possible way to reimagine techniques courses is by establishing core teaching practices , which are high-frequency teacher behaviors that are developed and mastered over time to provide a common pedagogical vocabulary about foundational knowledge and skills for the classroom (Abramo, 2015; Millican & Forrester, 2019). Millican and Forrester (2019) suggested that the most important core practices for music teachers are relationship building, modeling, and sequencing. They noted that specific music skills were not considered in their survey study but were addressed by participants through open-ended questions.…”
Section: Core Teaching Practices and Constructivism In Techniques Cou...mentioning
confidence: 99%